Pressured to perform - Bonginkosi Hardy Mutongoza (University of Johannesburg, 2023)
A growing body of work suggests that junior researchers in universities are often confronted by an unfathomable pressure to conduct research and get published in order to scale up the academic ladder. These pressures are often loaded with little to no regard for the welfare of the junior academics and no concern for the career paths to be taken. Against this background, this study explored the negative consequences associated with the pressure to publish from the unique perspective of junior academics at a rural university in South Africa. The study was underpinned by a qualitative research approach which enabled the utilisation of qualitative interviews with twelve junior academics from four faculties at the university. The findings demonstrated the often-salient bullying and abuse of junior academics that happens under the guise of mentorship from their senior colleagues. The study also revealed the cost at which the pressure to perform comes, namely the cost to mental well-being, the temptation to publish in predator journals, the rise of unethical publishing, and the sacrifice of quality research. Based on these findings, the study recommended that more considered efforts be made to secure the welfare of emerging academics and that more concerted efforts be instituted in universities to guard against the rise of academic bullying at the hands of senior academics.